Accounting Information Quality From The Perspectives Of Msmes Operating In The State Of Arunachal Pradesh, India (Journal of Informatics Education and Research, 2023)
The study strives to assess Accounting Information Quality (AIQ) of MSMEs in Arunachal Pradesh from the perspective of Sector and Type of Enterprise. The primary purpose was to see if AIQ of MSMEs is affected by Sector where they operate or Type of Enterprise they are. Sector includes Manufacturing and Service, whereas Micro, Small and Medium were the Type of Enterprise considered for the present study. The study used a schedule questionnaire targeting 290 MSMEs across various districts of Arunachal Pradesh. To arrive at the desired results, Independent sampled t-Test and ANOVA test were conducted. The findings reveal no statistically significant mean differences in AIQ among the MSMEs in Arunachal Pradesh when they were classified based on the Sector in which they operate and enterprise type under which they are classified. The study finally concludes in line with the findings that AIQ of MSMEs shares no significant relationship either with the Sector or the Type of Enterprise. Whether they are Micro or Small or Medium Enterprises belonging to Manufacturing or Service sector, AIQ observed through survey remains unaffected.